Implementing Jigsaw Cooperative Learning to Improve Fourth-Grade Indonesian Language Outcomes - Pase, Moeh Ilham; Wilade, Surahman; Aqil, Moh; Hariana, Kadek (Papanda Publisher, 2025)
Elementary Indonesian language instruction faces persistent challenges including passive learning environments, limited student engagement, and suboptimal academic achievement. This study investigated the effectiveness of the Jigsaw cooperative learning model in enhancing teacher instructional skills, student learning activities, and academic outcomes in fourth-grade Indonesian language learning. A Classroom Action Research design following Kemmis and McTaggart's cyclical model was implemented across two cycles at SD Negeri Ambesia involving 27 fourth-grade students. Data were collected through achievement tests, structured observation sheets, and semi-structured interviews, then analyzed using descriptive statistics and thematic analysis. Teacher instructional performance improved significantly from fair (66%) in Cycle I to very good (82.5%) in Cycle II. Student learning activities increased from fair (66%) to very good (87%), demonstrating enhanced engagement and collaborative behaviors. Academic achievement showed substantial improvement, with classical mastery rising from 70.4% to 92.5%, exceeding the 85% target criterion. The mean score increased from 69.2 to 75.1 between cycles. The Jigsaw cooperative learning model effectively enhances teacher competence, student engagement, and learning outcomes in elementary Indonesian language instruction. These findings support broader implementation of cooperative learning strategies in rural educational contexts with appropriate professional development support.